2018
DOI: 10.1029/2018gl078287
|View full text |Cite
|
Sign up to set email alerts
|

Local Excitation of Whistler Mode Waves and Associated Langmuir Waves at Dayside Reconnection Regions

Abstract: In the Earth's dayside reconnection boundary layer, whistler mode waves coincide with magnetic field openings and the formation of the resultant anisotropic electrons. Depending on the energy range of anisotropic electrons, whistlers can grow at frequencies in the upper and/or lower band. Observations show that whistler mode waves modulate Langmuir wave amplitude as they propagate toward the X line. Observations of whistler mode wave phase and Langmuir waves packets, as well as coincident electron measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 56 publications
5
38
0
Order By: Relevance
“…In this context, the paper by Drake et al (2015) should be mentioned. A more direct indication for the acceleration of electrons by wave‐particle interaction is seen in the chorus wave modulation of Langmuir waves (Li JX et al, 2017, 2018).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In this context, the paper by Drake et al (2015) should be mentioned. A more direct indication for the acceleration of electrons by wave‐particle interaction is seen in the chorus wave modulation of Langmuir waves (Li JX et al, 2017, 2018).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In the Earth's magnetosphere, whistler mode waves can be generated by electron temperature anisotropy ( T ⊥ > T ∥ ) (Kennel & Petschek , ; Li et al, ) or electron beams (Ren et al, ; Sauer & Sydora, ). In this study, the whistler mode waves are generated by electron populations streaming on one side along the magnetic field and such a mechanism resembles the whistler heat flux instability (WHFI) (Kuzichev et al, ; Tong, Vasko, Marc, et al, ) observed in the solar wind.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…However, the hiss‐driven Landau damping process can generate a field‐aligned population at Landau resonant energies rapidly, as shown in our case. The parallel acceleration produces a smaller PSD gradient in the parallel direction ( ∂f / ∂v ∥ ) or even a possible PSD plateau (e.g., Agapitov et al, ; An et al, ; Li et al, ; Min et al, ), which can significantly weaken or even eliminate further Landau damping ( W . Li et al, ; Ma et al, ).…”
Section: Discussionmentioning
confidence: 99%